Promoting physical activity-related health competences in people with intellectual disability. (30th September 2020) - Bruland, D; Mauro, A; Latteck, ÄD
Abstract: Background: Physical inactivity is a global health problem. Physically active people show lower rates of chronic diseases or mortality. People with intellectual disabilities (PWID), a vulnerable group for health problems, have significantly lower levels of physical activity (PA) than general population. Due to reduced cognitive abilities, communicative and literacy skills, PWID have less access to health programs. Target-group-oriented interventions are rare. Methods: Methodological triangulation to survey PA-related health competences in all 3 subcategories: 3 participating observations and 24 interviews with PWID (inclusion criteria for both: mild or moderate ID); staff online survey (n = 67), all in an integration assistance institution. Participatory approach: 2 expert groups with PWID advise researchers e.g. validating results. Results: As expected, movement abilities and body awareness various highly from general population. An effect knowledge is widely spread (PA = health), but execution knowledge of PA is only marginally available e.g. not knowing how to increase PA healthy. Control competences as results from interview and observations: intrinsic motivation is highly present (unlike results from staff survey), but volition - self-efficacy and bring into action - is very poor, self-management and a lack of ideas are identified as a major problem. Low expectation of self-efficacy proved to be the biggest obstacles for PA, but caregiver are an own health resource. Expert groups confirm important of PWID perspectives on living environment. Conclusions: To promote a PA lifestyle, health education with a focus on promoting self-efficacy orientated to the living environment (incl. caregiver) regarding own perspectives and health resources is needed. In this way, a vulnerable group for health problems can be empowered. Results indicate a successful approach to promote PA-related health competences in PWID to minimize health inequalities in relation to general population. Key messages: Health inequalities among people with intellectual disability through promoting a PA lifestyle can be minimized. Intervention for people with intellectual disabilities must take into account the perspectives and the resources of the users.